Apoio social e evasão escolar em gestantes adolescentes assistidas na estratégia de saúde da família do município de Sobral - Ceará - Sousa, Carla Roberta Macedo de (2013)
The school dropout is a risk that pregnant adolescents submits themselves and may bring repercussions in their professional future, in the socioeconomic conditions of the new family, and in her self-esteem. According to DATASUS, the incidence of pregnancy in this life cycle, between 2009 and 2010 in Brazil, ranged from 16.27% to 25.96%. The literature on the subject still has research gaps, particularly regarding the role of social support in preventing this event. The aim of this study was to describe the nature of the relationship between perceived social support and school dropout in pregnant adolescents assisted in the Family Health Strategy in Sobral’s municipality. The theoretical frame of reference chosen to develop the study was the Social Support theory, which focuses on transactions between individuals and their social networks, satisfying their social needs, promoting and completing personal resources they need to have to face the possible adversities imposed. The approach of the study was qualitative and the participants were 20 pregnant women aged 14 to 19 years, assisted during prenatal in Sobral’s Family Health Strategy. It was used as a technique for data collection a structured interview, and as technical analysis the Collective Subject Discourse. We followed the guidelines and standards of research involving human being contained in Resolution 196/96 of National Health Council. Of the interviewed teenagers, 13 had escaped the school and 07 remained. As results’ we had that social support in pregnant adolescents in the city of Sobral, Ceará was perceived in its different dimensions, and the nature of perceived social support mainly originated from their social network, represented by these adolescents’ household in their structural perspective and functional outlook, affective, material, informational and positive social interaction. Social support in their affective and material dimensions was more perceived in relation to those families in that pregnant teenagers didn’t escape the school. Pregnant women who escaped the school had a conflictive relationship with her mother and father absence in their household. Pregnant women who didn’t escape the school beside counting on the emotional support of the family, represented mainly by the mother, had the material support to help care for the child after birth so that the teenager could return to studies and so, influencing positively their school. In the two groups weren’t perceived the school as a promoter of social support in any of the studied prospects. To sum up, the social support shows relation to school dropout in pregnant adolescents in Sobral’s city, Ceará